Eucalyptus-based livelihoods: enhancing household food security and resilience in Northwest Ethiopia - Belay, Fasika; Mulugeta, Messay; Makonnen, Teferee (Frontiers in Sustainable Food Systems, 2025)
Farmers in northwest Ethiopia have been transforming their livelihood strategies, however, the impact of this transformation on food security status and resilience is hardly investigated. The study aimed to analyze the contribution of livelihood strategy transformation to farmers' food security and capital assets in the Senan district, Ethiopia. A multistage sampling technique was utilized, and a total of 332 households were taken, of whom 166 households that had transformed their livelihood strategy, and 166 households had not. The results of the independent sample t-test revealed a statistically significant difference in average scores for the Household Food Insecurity Access Scale (M = 8.06 compared to 11.29) and the Household Dietary Diversity Score (M = 5.28 compared to 4.73) between households with and without eucalyptus plantations. The econometric analysis revealed that variables such as total land holding size, annual income, and livelihood diversification had a positive influence on the probability of a household being categorized as food secure. Moreover, the outcome of the livelihood asset index reveals that households that possess eucalyptus plantations exhibit higher indices for natural, physical, financial, and social assets compared to households without plantations. However, households that own eucalyptus plantations demonstrate a lower index for human capital than those without eucalyptus plantations. These findings underscore the role of eucalyptus plantations in enhancing food security and improving livelihoods for farmers in the study area. Furthermore, diversifying income sources through eucalyptus plantations can significantly amplify its overall benefits for local households.